Excitation mechanisms of C II optical permitted lines in ionized nebulae - Reyes-Rodríguez, Elena; Méndez-Delgado, José Eduardo; García-Rojas, J.; Binette, L.; Nemer, A.; Esteban, C.; Kreckel, Kathryn (Astronomy and astrophysics, 2024)
Context: Carbon is the fourth most abundant element in the universe and its distribution is critical to understanding stellar evolution and nucleosynthesis. In optical studies of ionized nebulae, the only way to determine the C/H abundance is by using faint C II recombination lines (RLs). However, these lines give systematically higher abundances than their collisionally excited counterparts, observable at ultraviolet (UV) wavelengths. Therefore, a proper understanding of the excitation mechanisms of the faint permitted lines is crucial for addressing this long-standing abundance discrepancy (AD) problem. Aims: In this study, we investigate the excitation mechanisms of C II lines λλ3918, 3920, 4267, 5342, 6151, 6462, 7231, 7236, 7237, and 9903. Methods: We use the DEep Spectra of Ionized REgions Database (DESIRED) that contains spectra of H II regions, planetary nebulae and other objects to analyze the fluorescence contributions to these lines and the accuracy of the atomic recombination data used to model the C+ ion. Results: We find that C II λλ4267, 5342, 6151, 6462, and 9903 arise exclusively from recombinations with no fluorescent contributions. In addition, the recombination theory for these lines is consistent with the observations. Our findings show that the AD problem for C2+ is not due to fluorescence in the widely used C II lines or errors in their atomic parameters, but to other phenomena such as temperature variations or chemical inhomogeneities. On the other hand, C II λλ3918, 3920, 6578, 7231, 7236, 7237 have important fluorescent contributions, which are inadvisable for tracing the C2+ abundances. We also discuss the effects of possible inconsistencies in the atomic effective recombination coefficients of C II λλ6578, 7231, 7236, and 7237.